Bale Mediation as an Alternative Institution For Resolution of Communal Intellectual Property Rights Disputes Among Indigenous Communities in West Nusa Tenggara - Atsar, Abdul; Fathoni, Lalu Achmad (Universitas Islam Malang, 2024)
The settlement of communal intellectual property rights disputes is not only through litigation, but is also possible through mediation. The purpose of this study is to determine the position of the mediation hall as an alternative institution in resolving communal intellectual property disputes and in the judicial system in Indonesia and how the legal force of the Bale Mediation decision is in resolving Communal Intellectual Property disputes. This research method uses normative legal research, namely legal research conducted by examining library materials or secondary data. Based on the results of the study, Bale Mediation is an institution that carries out the functions of mediation, coaching and coordination in the implementation of mediation in the community in accordance with local wisdom in the context of legal reform in the field of resolving Communal Intellectual Property Rights disputes. Bale Mediation is not part of the state judiciary but rather an institution that resolves disputes outside the courts. Legal settlement of Communal Property disputes through Bale Mediation is a non-structural institution and is responsible to the Governor. The decision or result of the dispute resolution at the Mediation Center in the form of an agreement that does not yet have permanent legal force but is only an ordinary contract for the parties, only obtains the status of a peace deed after the parties, with or without the assistance of a mediator, file a peace lawsuit through the Commercial Court/District Court.